Enhancement of oral bioavailability of E804 by self-nanoemulsifying drug delivery system (SNEDDS) in rats - Heshmati, Nasim; Cheng, Xinlai; Eisenbrand, Gerhard; Fricker, Gert (Journal of pharmaceutical sciences, 2016)
Indirubin and its derivatives have been shown to interrupt the cell cycle by inhibiting cyclin-dependent kinases, explaining their long-time use in traditional Chinese medicine for the treatment of chronic myelocytic leukemia. A potent derivative of indirubin, indirubin-3′-oxime 2,3-dihydroxypropyl ether (E804), has been shown to block the Src-Stat3 and Src-Stat5 signaling pathway in human cancer cells, inducing apoptosis. The anticancer effects of E804, however, cannot be easily examined in vivo because of its poor water solubility and low absorption. The aim of this study was to develop and evaluate a self-nanoemulsifying drug delivery system (SNEDDS) containing E804 for enhancing its solubility and bioavailability. Solubility of E804 was determined in various vehicles, and pseudoternary phase diagram was used to evaluate the self-emulsifying existence area. The SNEDDS composed of Capmul MCM (oil), Solutol HS 15 (surfactant), and polyethylene glycol 400 (cosurfactant) on the ratio of 20.5:62.5:16 loaded 1.5% of E804. The particle size of droplets was found to be 16.8 and 140 nm, and SNEDDS was stable after freeze-thaw cycles and upon dilution in HCl 0.1 N and pH 7.4 HBSS++. The ability of formulation for absorption enhancement was studied in rats in vivo after oral administration. The results showed that the developed SNEDDS increased the E804 bioavailability 984.23% compared with the aqueous suspension. Our studies for the first time show that the developed SNEDDS can be used as a possible formulation for E804 to improve its solubility and oral bioavailability. © 2013 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 102:3792-3799, 2013
Gesehen am 29.04.2021
Available online 4 January 2016